An evaluation ofthe Allostatic Load framework for quantifying differences inhealth and longevity - McLoughlin, Sinead Niamh (Trinity College Dublin. School of Medicine. Discipline of Medical Gerontology, 2023)
The Allostatic Load (AL) framework posits that chronic or repeated exposure to stressors can cause dysregulation of multiple interrelated physiological systems, which if prolonged, may ultimately lead to deteriorations in health. Since its conceptualisation in the early 1990s, research on AL has grown steadily, showing promise as a sub-clinical predictor of poor health outcomes, and is known to be patterned by socio-economic position (SEP). AL is typically indexed using a composite index of biomarkers across multiple systems, yet no gold standard operational definition exists. This has brought about a large heterogeneity of biomarkers and techniques to instantiate the concept, complicating comparisons of results across studies and stunting the development of the framework. This thesis addresses several of the limitations within the extant literature using the rich psychosocial and biological data from Wave 1 of The Irish Longitudinal Study on Ageing (TILDA). Specifically, it addresses: (1) whether the method of calculating composite biomarker indices impacts the predictive utility AL on health outcomes, (2) the extent of the association of life course stress exposure with AL, (3) whether mobility in/ out of social disadvantage across the life course moderates AL burden, and (4) the association of a large suite of biomarkers with stress and all-cause mortality. The results of this evaluation can be used to help inform the development of AL indices. Recommendations for future research to develop the AL framework include longitudinal analysis to further understand the causal mechanisms underlying the pathway to poor health from exposure to adverse events over the life course. Additionally, researchers in the field should attempt to broaden the measures applied in relation to the AL index and incorporate dynamic measures of physiological functioning.
APPROVED
Keywords: pyschosocial; stress; Ireland; biomarkers; ageing; allostatic load